Pengaruh Kuliah Daring dan Tatap Muka Terhadap Motivasi Belajar Mahasiswa pada Masa Pandemi COVID-19 - Irma Irma; La Ode Liayaumi Azim; Kamrin Kamrin (NHM PRESS, 2022)
COVID–19 is an infectious disease caused by a virus with very high transmission and in a short time can cause a global pandemi. The COVID–19 pandemi situation has also rapidly changed and affected people's life challenges, including the world of education. This study aims to analyze the effect of online and face-to-face learning on the learning motivation of students majoring in public health, Faculty of Public Health, Halu Oleo University in 2022. This research is an observational analytical study with a cross-sectional study design with a total sample of 125 which is calculated based on the slovin (n) formula. =N/1+N(d)2 and taken using probability sampling technique with simple random sampling technique. The statistical analysis used was the paired-t-test (α = 0.05). The results show that the test results with pvalue = 0.005 <α=0.05 means H1 is accepted and H0 is rejected.Thus it can be concluded that there is the effect of online and face-to-face lectures on the learning motivation of students majoring in public health, Faculty of Public Health, Halu Oleo University in 2022. Further research is needed to see which lecture or learning methods are most influential and effective during the COVID–19 pandemi.